DCOOD optically pumped by a (CO2)-C-13 laser: New terahertz laser lines - Viscovini, Ronaldo C. (2008)
In this work, we report new optically pumped terahertz laser lines from DCOOD. An isotopic (CO2)-C-13 laser was used for first time as pump source, and a Fabry-Perot open cavity was used as a terahertz laser resonator. Optoacoustic absorption spectra were used as a guide to search for new terahertz laser lines. We could observe six new laser lines in the range from 303.8 mu m (0.987 THz) to 725.1 mu m (0.413 THz). The lines were characterized according to wavelength, relative polarization, relative intensity, and optimum working pressure. The transferred Lamb-dip technique was used to measure the frequency absorption transition both for this laser lines.